Efektivitas Getah Pohon Jarak Cina Terhadap Perkembangan Kolonisasi Bakteri Luka Insisi Pada Hewan Coba Mus Musculus Strain Balb/C - Suyatno Hadi Saputro; Nugroho Ari Wibowo (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
The purpose of this study was to determine the effectiveness of Chinese jatropha sap on the development of incision wound bacteria colonization in experimental animals Mus musculus Strain Balb / cThe design of this study used a true experiment post only control group design by administering Chinese jatropha tree sap to male mice (bal mus / musculus) strains aged 2 to 2.5 months and weighing 20-30 grams with a total of 30 mice. Mice made incision wounds and observed the number of colonies in the inflammatory and proliferation phases of Chinese jatropha sap and compared with bioplacentonsThe results of the study in the treatment group were 410 bacteria on average while the control group were 585 bacteria in the inflammatory phase. Furthermore, in the proliferation phase the treatment group averaged 39 bacteria while in the control group there were an average of 79 bacteria. Independent t-test results in the inflammatory phase showed that Ñ€ = 0.042 <Î± = 0.05 Furthermore, in the proliferation phase Ñ€ = 0.041 <Î± = 0.05, in both phases there was an effect of giving Chinese jatropha tree sap to the amount of bacterial colonization in animals try Mus musculus Strains Balb / c.Chinese jatropha tree sap contains alkaloids, saponins, flavonoids, tannins, and anti-microbial Î²-lactams so as to stop the development of bacterial colonies in wounds. It is hoped that the Chinese jatropha sap can be an alternative in the initial treatment of open wounds and incisions in the limitations of medicine when a disaster occurs.